PELATIHAN DESAIN PRODUK DAN IKLAN DIGITAL UNTUK KARANG TARUNA KELURAHAN GAJAHMUNGKUR - Muhammad Noor Hidayat; Zahrotul Umami; Muhammad Hasan Bashori (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2020)
Product design become more important thing for traditional snack producers, especially jajan pasar, which is the term for traditional snack in the Semarang and Central Java Region. The design of packaging and digital advertising is also a supporting tool in marketing of jajan pasar. The development of creativity and product packaging innovation is the key to achieving success for the business being run. Product packaging is a way for consumers to judge a product both in the terms of benefits, aesthetics and quality of the product. The unique product design is an added value in marketing of jajan pasar through digital advertising. Jajan pasar are the potency of Gajahmungkur, but this potential is not supported by packaging design and digital advertising in expanding marketing. Seeing this problem, the communication science lecturer cooperated with Karang Taruna Gajahmungkur to create a public service program about the importance of digital advertising supported by a unique packaging design to increase the marketing of jajan pasar in the Gajahmungkur. Public service activities regarding packaging design and digital advertising are expected to be able to help the people of Gajahmungkur in marketing jajan pasar product so that they can improve the prosperity of Gajahmungkur communities